The Analysis of Labor Demand of the Private sector in the Northern Provinces of Lao PDR: https://doi.org/10.69692/SUJMRD1001222 - SIOUDOMPHAN, Soutthavone; CHANTHAVONE, Thongphanh; SIPHANTHONG, Bounthavy; DUANGPASITH, Phatsa; Phommany, Sombath; PHANTHOUAMATH, Phoutthalack; CHITTAPHONE , Namfonh; KEODOUANGKHAM, Phavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research aims to study the structure of labor market in private sector, analyze the labor demand of the private sector labor market and analyze the factors affecting the labor demand of the private sector labor market in the northern provinces of Lao PDR. Using a critical random sampling method, the instrument used to collect data is a questionnaire and analyze data with descriptive statistics percentage value, average value, standard deviation value and estimated statistics are: Chi-square the analysis of the data found that: The structure of the private sector labor market in the northern provinces of Lao PDR. In general, there are small and medium-sized businesses with less than 5 workers and most of them are Lao workers who come from within the province and from outside the province. There are a few foreign workers, mainly from neighboring countries such as Thailand, Vietnam and China. Mainly there is a shortage of workers in the field of expertise workers and specialized workers. At the same time, there is also a demand for labor or marketing and production staff. And there is a need for labor between 1-2 people; Have a bachelor's degree or higher and major in trade, hotel management and food science, mechanist and business administration. From the results of testing the relationship, it was found that: the characteristics of the labor are related or have an effect on the demand for the number of workers, the experience of the labor, the age of the labor, the status of the labor and the educational qualification of the labor, but there is no relationship with the needs of the gender and the specific subject of the labor; External factors to the business have a relationship with labor demand in terms of labor status, work experience, number of labor, age of labor, but there is no relationship with labor demand, labor education, and labor specialization. The internal business factor has a relationship with the need for labor experience but has no relationship with other needs with a statistical significance level of 0.05 and 0.01 respectively.